AODWE-005 Golimumab induction for moderate to severe ulcerative colitis: patient-reported outcomes of partial mayo score results from the go-colitis study. (17th June 2017) - Sebastian, S; Probert, C; Gaya, D; Hamlin, PJ; Irving, P; Gillespie, G; Tate, H; Wheeler, C
Abstract : Introduction: GO-COLITIS is a multicentre, open-label, single-arm, phase 4 study (NCT02092285 ; 2013-004583-56) that measured efficacy of subcutaneous golimumab (GLM) in anti-tumour necrosis factor-naïve UK patients with moderate to severe ulcerative colitis (UC) despite conventional treatment. Results of the patient-reported outcomes (PROs) of the partial Mayo score from the 6 week induction phase are presented here. Method: Adults with UC ≥3 months, moderate to severe disease (partial Mayo score 4–9 or Mayo score 6–12) at baseline (BL), Mayo rectal bleeding subscore ≥1, and Mayo endoscopy subscore ≥2 (if full Mayo was used) were included. Patients received GLM on day 0 (200 mg) and day 14 (100 mg) during the 6 week induction phase, followed by GLM 50 mg or 100 mg every 4 weeks during the 48 week maintenance phase as per the Summary of Product Characteristics, with 12 week follow-up. Measurements taken at BL and week 6 included the PRO components of the Mayo score. Results: Overall, 205 patients were enrolled (mean [range] age, 39.3 [18–79] years; male, n=123 [60%]) and received one (n=2) or two doses (n=203) of induction GLM. This resulted in pronounced improvements from BL to week 6 in the stool frequency (mean change, –1.1; SD, 1.0), rectal bleeding (mean change, –1.1; SD, 0.9), and physician global assessment (mean change, –1.1; SD, 0.9) subscores of the Mayo score (all p<0.0001). Improvements in stool frequency and rectal bleeding subscores included increased proportions of patients with normal scores and decreased proportions with severe scores at week 6 versus BL (table 1). Conclusion: Patients with moderate to severe UC experienced significant improvements from BL to week 6 in the PROs of the partial Mayo score. These changes parallel the significant improvements found in the physician global assessment and patient-reported quality of life (EQ-5D/IBDQ) at week 6 versus BL. 1 Rectal bleeding and stool frequency PROs of the Mayo score could thus be a simple and noninvasive way for patients with UC to monitor their response to treatment in daily clinical practice. References: . P Irving, et al. ECCO2016; Poster P310. Disclosure of Interest: S Sebastian Conflict with: Abbvie, Ferring, Warner Chilcott, Conflict with: Abbvie, Takeda, Warner Chilcott, Conflict with: Falk Pharma, Ferring, MSD, Takeda, Vifor, Warner Chilcott, C Probert Conflict with: Abbvie, MSD, Napp, Takeda, Conflict with: Abbvie, Falk, Ferring, MSD, Shire, Takeda, Conflict with: Abbvie, Falk, MSD, Shire, Takeda, D Gaya Conflict with: Abbvie, Dr Falk Pharma, Ferring, MSD, Shire, Takeda, Vifor, Conflict with: Abbvie, Dr Falk Pharma, Ferring, MSD, Shire, Takeda, Vifor, P Hamlin Conflict with: MSD, Abbvie, Warner Chilcott, Ferring, Tillotts, Takeda, Conflict with: MSD, Abbvie, Tillotts, Falk Pharma, P Irving Conflict with: MSD, Takeda, Conflict with: Abbvie, Warner Chilcott, Ferring, Falk Pharma, Takeda, MSD, Johnson and Johnson, Shire, Conflict with: Abbvie, Warner Chilcott, Takeda, MSD, Vifor Pharma, Pharmacosmos, Topivert, Genentech, Hospira, G Gillespie Conflict with: MSD UK, Conflict with: Merck and Co., Inc., H Tate Conflict with: GSK, Conflict with: MSD UK, C Wheeler Conflict with: Shield Therapeutics, Tesaro, Clovis Oncology, Novelion, Conflict with: MSD, Daiichi Sankyo, Takeda, GSK, AstraZeneca, Aegerion, Sanofi, Amryt Pharma, Shionogi